Wiener-Hopf analysis of the dominant mode propagation in a dual-ridged parallel plate waveguide with impedance loading - Alkumru, A; Büyükaksoy, A; Günes, F (TAYLOR & FRANCIS INC, 2002)
The dominant mode propagation in a parallet-plate waveguide with impedance-loaded interacting step discontinuities is analyzed rigorously through the Wiener-Hopf technique. Introducing the Fourier transform of the scattered field and applying the boundary conditions in the transform domain, the problem is reduced to a modified Wiener-Hopf equation of the third kind and solved approximately, Some numerical results displaying the effects of the surface impedance of the steps as well as their thicknesses and lengths on the reflection and radiation phenomenon are presented.
Keywords: waveguide; impedance loading; step discontinuities; Weiner-Hopf technique; Engineering